PENGEMBANGAN MODUL EDUKASI SINGLE PARENT ANAK JALANAN - Kurnia Vivi Elida; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstarct: The objectives of this research to develop a single parent for street children education module in terms of material clarity, material systematics, image support, the suitability of material delivery time, material completeness, module accuracy, module usability, and module feasibility. The research method used is Research and Development (R&D). The steps used are (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, and (6) product manufacturing. The instruments of this research are the validation sheets to get the feasibility test results, while the validators in this study is 2 validator material guidance counseling and 2 guidance counseling practitioners. The results of the study showed that a single parent education module for street children in terms of every aspect, namely (1) Quality in the aspect of material clarity is 79.16% with the